Variability in leaf Traits of 14 Native Woody Species in Semiarid Regions of Northeastern Mexico - Maiti, Ratikanta; Gonzalez-Rodriguez, Humberto; Karfakis, Theodore (International Journal of Bio-resource and Stress Management, 2023)
The present study was undertaken with the goal of analyzing the morphology and variability of leaf length, width, petiole length, and total leaf length, fresh and dry weight of individual leaves of 14 species native to Northern Mexico. The native species Cordia boissieri, Condalia hookeri, Sargentia greggii, Diospyros texana, Zanthoxylum fagara, Sideroxylon celastrinum, Karwinskia humboldtiana, Celtis pallida, Guaiacum angustifolium, Prosopis laevigata, Celtis laevigata, Parkinsonia texana, Forestiera angustifolia and Havardia pallens where chosen due to their ecological and economic importance to the rural villages as well as large variability in morphological characteristics between them. Descriptive statistical analyses showed that there was large variability in these leaf traits between the different species. Principal component analysis (PCA) revealed that it was possible to produce two axes that can explain more than 83% of the observed variation and could therefore be used in the future for separating tree species in ecological guilds and to study. Species and vegetation community level response to perturbations or individual performance in the field or under experimental conditions between the different species of this study. This suggests that similar advances are possible for other species for the same traits both in the region of study but also elsewhere.